Brown and Levinson's politeness framework and studies on politeness in the 1990s - Lim, Beng Soon (Journal of Modern Languages, 2017)
This paper discusses the theoretical framework of Brown and Levinson (1987) focusing on the dissenting opinions in recent literature on politeness. It focuses on some of the major works in the last decade that have debated the practicality of operationalizing Brown and Levinson's framework either cross-culturally or in western societies.